PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTU INSTAGRAM TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA KELAS X SMA NEGERI 8 SURAKARTA - Rina Putri Utami; Riezky Maya Probosari; Umi Fatmawati (Universitas Sebelas Maret, 2015)
The purpose of this research was to know the influence of Project-Based Learning models by Instagram toward creative thingking of tenth grade students at SMA negeri 8 Surakarta. The research was a quasi experimental research which used posttest only non-equivalent control groups as a research design. The population in the reserach was the students of tenth grade in the second semester of SMA Negeri 8 Surakarta. The sampling technique used cluster sampling. The collecting data were by test and non test method. The method was essay question of creative thingking and the non test method using observation, and documentation. Hypothesis test were analysed by t-test using SPSS version 16. The research results were received H1 and H0 rejected. It means there was a difference of student creative thingking between control class with conventional models and experiment class using Project-Based Learning models by Instagram. The conclusion of the research was there was the influence of Project-Based Learning models toward increase creative thingking of tenth grade students at SMA Negeri 8 Surakarta. Keywords: Project Based Learning,Instagram, Creative Thingking